Fluency Interventions for Struggling Readers in Grades 6 to 12: A Research Synthesis. (January 2022) - Steinle, Paul K.; Stevens, Elizabeth; Vaughn, Sharon
This systematic review synthesizes fluency intervention research for struggling readers in Grades 6 through 12 from January 2006 to October 2019. The search yielded 17 studies examining reading fluency and comprehension outcomes. Most studies examined repeated reading (RR) interventions to improve reading fluency for struggling readers at these grade levels, resulting in improved fluency but few positive effects on reading comprehension outcomes, similar to trends observed in prior systematic reviews. Reading connected text with an equivalent word count to word counts of RR sessions did not result in increased reading fluency, a finding aligned with a prior synthesis. Few studies used a fluent reader as a model prior to RRs, despite previous support for modeling within fluency interventions.